Antimonite regulation of the ATPase activity of ArsA, the catalytic subunit of the arsenical pump. - Walmsley, A R (2001)
The ArsA ATPase is the catalytic subunit of the pump protein, coupling the hydrolysis of ATP to the movement of arsenicals and antimonials through the membrane-spanning ArsB protein. Previously, we have shown the binding and hydrolysis of MgATP to ArsA to be a multi-step process in which the rate-limiting step is an isomerization between different conformational forms of ArsA. This isomerization occurs after product release, at the end of the ATPase reaction, and involves the return of the ArsA to its original conformation, which can then bind MgATP. ArsA possesses an allosteric site for antimonite [Sb(III)], the binding of which elevates the steady-state ATPase activity. We have used a transient kinetics approach to investigate the kinetics of ternary complex formation that lead to an enhancement in the ATPase activity. These studies revealed that ArsA exists in at least two conformational forms that differ in their ligand binding affinities, and that ATP favours one form and Sb(III) the other. Ternary complex formation is rate-limited by a slow transition between these conformational forms, leading to a lag in attaining maximal steady-state activity. Sb(III) enhances the steady-state ATPase activity by inducing rapid product release, allowing ArsA to adopt a conformation that can bind MgATP for the next catalytic cycle. In the presence of Sb(III), ArsA avoids the rate-limiting isomerization at the end of the ATPase reaction and ATP hydrolysis becomes rate-limiting for the reaction. The binding of Sb(III) probably results in more effective pumping of the substrates from the cell by enhancing the rate of efflux.